Progressive Friction Mobilization and Enhanced Janssen S Screening in Confined Granular Rafts - Melo-Hurtado, F; Elettro, H (American Physical Society, 2018)
Confined two-dimensional assemblies of floating particles, known as granular rafts, are prone to develop a highly nonlinear response under compression. Here we investigate the transition to the friction-dominated jammed state and map the gradual development of the internal stress profile with flexible pressure sensors distributed along the raft surface. Surprisingly, we observe that the surface stress screening builds up much more slowly than previously thought and that the typical screening distance later dramatically decreases. We explain this behavior in terms of progressive friction mobilization, where the full amplitude of the frictional forces is only reached after a macroscopic local displacement. At further stages of compression, rafts of large length-to-width aspect ratio experience much stronger screenings than the full mobilization limit described by the Janssen s model. We solve this paradox using a simple mathematical analysis and show that such enhanced screening can be attributed to a localized compaction front, essentially shielding the far field from compressive stresses. © 2018 American Physical Society.